Functions of Bibliographical Modeling - Лиров, В.П. (Knygotyra, 1973)
In this article it is proposed the new interpretation of bibliography as a special mean to model intelectual progress. The main aspects of bibliographical modeling (registration of documental materials, control after used literature, making researches of literature etc.) are examined just from this point of view.